Paediatric endocrinology curriculum content uniformity across medical schools in Southern Nigeria - Lecturers' report (Educational Dimension, 2023)
The Medical and Dental Council of Nigeria (MDCN), the regulatory body for medical practice in Nigeria, provides the benchmark for minimum academic standards (BMAS). While it is expected that there will be differences across schools, the extent of this is unknown and the effect/impact it will have on future medical practice in Nigeria is unknown. This study aimed to evaluate the differences in undergraduate paediatric endocrinology contents across medical schools in southern Nigeria and to understand the factors that influence these differences. Seven paediatric endocrinology lecturers were interviewed, and they filled a questionnaire generated from the themes of the discussion. The themes included the contents of diabetes mellitus lectures, the level of participation lecturers allowed students in emergency room management of DKA, and the assessment methods. Lecture notes on diabetes mellitus (DM) were scored using ISPAD guidelines and the differences were analysed using Student’s T test. The extent to which competence was assessed for students was also provided by the lecturers. Two lecturers had reduced contents in their DM lectures, compared to others, $p = 0.003$. Most lecturers did not consult the MDCN BMAS while preparing their lecture notes. This study highlights the differences in curriculum contents in Southern Nigeria medical schools for endocrinology training in paediatrics, and significant differences methods of training. These differences will hamper the core objectives of human capital development should the trend continue. It is recommended that uniform curriculum template that is acceptable to many to streamline training and medical practice.